Utilize the least square method to quantify the perimeter of gastrointestinal stromal tumour - Rathi, Sidik; Harun, Nurzalina; Muhammad Fazlee, Nur Fareesha; Sadikin, Zubaidah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
This study focuses on calculating the arc length of gastrointestinal stromal tumours (GISTs) to determine the tumour's perimeter using the least-squares method. The method involves developing a mathematical equation that corresponds to the tumour model to calculate the perimeter even under uneven conditions. Least squares is used to find the best-fit line or curve that minimizes the sum of squared differences between observed data points and predicted values, commonly used in regression analysis. For tumour perimeter calculation from ultrasound data, the study employs both the least squares method and the Gauss-Jordan elimination method. By determining that 1 mm on the graph paper corresponds to 1.2929 mm in actual size, the total arc length is calculated to be 9.5026 mm. Manual measurements, especially with complex shapes and small details, can be prone to errors. Therefore, PeriSolve, a graphical user interface (GUI) and professional simulator, is designed to simplify perimeter calculations for uneven surfaces, with a specific focus on using the least squares method.